Society and individual in Renaissance Florence - Connell, William J. (University of California Press, 2002)
Renaissance Florence has often been described as the birthplace of modern individualism, as reflected in the individual genius of its great artists, scholars, and statesmen. The 16 essays in this volume explore fresh approaches to the social world of Florentines during this fascinating era.